CYBB identified as a key immune hub gene linking lung cancer and atrial fibrillation - Tong Lang; Lingbing Meng (Journal of Cardiothoracic Surgery)
Abstract Background The proportion of patients with lung cancer complicated by atrial fibrillation (AF) is increasing. Identifying shared molecular targets between these two conditions may provide important prognostic insights for patients with comorbidities. Methods The GSE8569 and GSE41177 datasets were downloaded from the Gene Expression Omnibus (GEO) database. Differential expression analysis was performed using the limma package in R. Weighted gene co-expression network analysis (WGCNA) was conducted to identify significant gene modules. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses, along with gene set enrichment analysis (GSEA), were used to explore biological functions. Clinical survival data for lung cancer were obtained from The Cancer Genome Atlas (TCGA), and receiver operating characteristic (ROC) analysis was conducted using the R package ROC (version 1.17.0.1). Results A total of 598 differentially expressed genes (DEGs) were identified. These DEGs were primarily enriched in cell proliferation, inflammatory responses, non-small cell lung cancer, the p53 signaling pathway, and the cell cycle. Three core genes (CYBB, ITGB2, FCER1G) were identified. Notably, CYBB was downregulated in lung cancer compared to normal tissue. Patients in the low-risk group had significantly better survival outcomes. Heatmap visualization showed that expression of CYBB decreased with increasing risk scores, suggesting a protective role. Conclusion CYBB expression may influence lung cancer prognosis and contribute to the pathogenesis of AF. Further research is needed to clarify CYBB’s role in patients with both conditions.